Zircon U–Pb Age and Deformation Characteristics of the Jiama Porphyry Copper Deposit, Tibet: Implications for Relationships between Mineralization, Structure and Alteration. Issue 4 (October 2014) - Duan, Jilin; Tang, Juxing; Mason, Russell; Zheng, Wenbao; Ying, Lijuan
Abstract: The Jiama copper deposit is one of the largest deposits recently found in Tibet and is composed of three types of mineralization including skarn, hornfels and porphyry. To investigate the relationship between mineralization, structure and alteration, we report new zircon U–Pb age and present field observations on the deformation characteritics associated with the copper mineralization in Jiama. Two main periods of deformation were identified, represented by D1 and D2 in Jiama. The first deformation (D1 ) occurred around 50 Ma, whereas the second deformation (D2 ) that was closely related to mineralization occurred later. Previous zircon U–Pb and molybnite Re–Os dating results indicate that the mineralizatoin occurred at ∼15 Ma and thus the D1 regional deformation significantly occurred before the mineralization time, although the D1 deformation probably provided important space for the development of significant copper deposition. Our new mapping and observations on the D2 deformation demonstrate that the mineralization was closely coeval with or slightly later than the time of D2 deformation. The new U–Pb zircon age further indicates that the aplite formed in ∼17.0 Ma and thus the D2 deformation happened later than this time because the D2 deformation cut across the aplite, which is proposed to be the key control for copper mineralization. Altered laminated hornfels including three types of alteration (A‐, K‐ and S‐type) were found spatially associated with the D2 deformation. The type‐A is mainly silicification, with fine sericite or chlorite, as well as abundant disseminated sulphides on fracture surfaces; the type‐S is mainly fine‐grained silicification with patches of chlorite, epidote and common sulphides; the type‐K (potassic alteration) appears to be fine‐grained biotite. Such types of alteration indicate the presence of skarns at depth where ore shoots are located. Taken together, the multiple structural‐magmatic‐mineralization events contributed to the formation of the supergiant Jiama porphyry copper deposit in Tibet. The results have general implication for regional exploration. Abstract : Two periods of deformation (D1 and D2 ) were identified in the Jiama copper deposit, Tibet, with the D1 deformation occurring earlier and the D2 deformation happening significantly later at 17 Ma based on new zircon U‐Pb dating results. The D2 deformation was the key control on copper mineralization which was coeval or slightly later than the D2 deformation.